PERANCANGAN BUKU RESEP MEMASAK KUE TRADISIONAL SUMATERA BARAT BERBAHAN DASAR KETAN - TISZA FERAHMA, Hendra Afriwan, S.Sn., M.Sn., Dra. Jupriani, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Not everyone knows how to make traditional cakes, especially West Sumatra local cakes made from rice  and glutinous rice flour which often appear in traditional events or family events. Meanwhile, a recipe book that specifically contains recipes from West Sumatra-based sticky rice cakes is still hard to find.The book "Cooking Traditional Cakes" Divided into three parts, namely the photo section that displays  photos of recipe-guided cakes, illustrations of baking ingredients and illustrations of how to make  cookies. Photos and illustrations are chosen to have an attractive appearance that is different from recipe books in general and aims to make information more easily and memorable. The purpose of designing  the book "Cooking Traditional Cake" is to make it easier for people to find information about the recipe for West Sumatra cakes, especially those made from sticky rice.In the problem solving process, 5W + 1H analysis is used (what, who, where, when, why, how) to find  solutions to the problems faced. In compiling prescription information, interviews and literature studies were carried out on the teachers of SMKN 9 Padang and the lecturers of the UNP Tata Boga Study  Program, then the results of the studies and observations were arranged in a simple layout and did not  confuse the user with a simple language style. To support the main media, supporting media are made, namely posters, Instagram accounts, aprons, spoons, post cards, bookmarks and stickers.Keyword : Books. recipes, illustrasion, cake, local.